Mobile Virtual Field Trip and Geography Education: Potential Exploration of Complex Problem Solving and Spatial Intelligence Capabilities - Izzah Salsabila, Tasyania; Putra, Alfyananda Kurnia; Matos, Teresa (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This study aims to determine the effect of M-VGFT media on students’ Complex Problem Solving and Spatial Intelligence abilities. Quasi-experimental research with post-test-only group design method. The design used two experimental groups with a purposive or judgment sampling method considering the average class value. X.2 Social Science group (14 boys and 20 girls), X.3 Social Science group (17 boys and 17 girls), and X.4 Social Science (17 boys and 17 girls). The subjects of this study were first-year high school students in the even semester of the 2021/2022 academic year. Hypothesis testing using independent sample t-test to determine the effect of M-VGFT media on the ability of students’ Complex Problem Solving and Spatial Intelligence in the subject of Geography on Volcanism. The results showed a significant influence between M-VGFT media on students’ Complex Problem Solving Ability and Spatial Intelligence in Madrasah Aliah Negeri Baru. However, there are differences in the influence between male and female students on the two variables.